Demand for aflatoxin‐safe maize in Kenya: Dynamic response to price and advertising - Hoffmann, Vivian; Moser, Christine; Herrman, Timothy J. (Agricultural and Applied Economics Association, 2021)
In countries where regulatory enforcement is weak, voluntary third‐party verification of firms' food safety processes can allow concerned consumers to select safer products. However, due in part to their legal ambiguity, and the potential to attract additional regulatory scrutiny, food safety claims are rarely made by firms. As a result, the impact of such claims on consumer demand is not well understood. We examine how labeling maize as tested for aflatoxin, a carcinogen also associated with stunting in children, affects sales. By randomly varying the timing and intensity of a marketing campaign to promote the first maize flour brand in Kenya labeled as tested for aflatoxin, we characterize dynamic consumer response to information about food safety. We find an immediate response in sales to marketing alone, which disappears as soon as marketing ceases. Sales remain elevated in the weeks after a temporary discount is offered, but this effect also fades over time and is not associated with greater awareness of the firm's food safety claims. These results suggest that it is unrealistic to expect for‐profit firms serving mass markets in low‐ and middle‐income countries to invest heavily in marketing based on food safety claims.